2000
DOI: 10.3109/s101650070011
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a revised Japanese version of the Arthritis Impact Measurement Scales version 2 (AIMS2)

Abstract: This study aims to evaluate the validity and reliability of a Japanese version of the Arthritis Impact Measurement Scales, version 2 (AIMS2) for patients with rheumatoid arthritis (RA). The Japanese version of the AIMS2 questionnaire was administered to 1643 patients with classical or definite RA at 11 hospitals nationwide in Japan. Reliability was assessed by a test-retest procedure, 4 weeks apart, using 75 randomly selected patients. Internal consistency was measured by Cronbach's α, and factor analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As mentioned above, we have explained patient’s health status based on subjective scales. Recently, health status scales such as SF-36 49 ) and the Arthritis Impact Measurement Scales, version 2 (AIMS2) 50 ) have been validated in a Japanese population and may be available in Japan. A quality of life scale for Japanese patients with intractable disease including SLE was also developed 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, we have explained patient’s health status based on subjective scales. Recently, health status scales such as SF-36 49 ) and the Arthritis Impact Measurement Scales, version 2 (AIMS2) 50 ) have been validated in a Japanese population and may be available in Japan. A quality of life scale for Japanese patients with intractable disease including SLE was also developed 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The Arthritis Impact Measurement Scales (AIMS) have been widely used to assess the health status of people with arthritis in many countries for years (1–9). Extensive testing and refinement have been done to make AIMS a reliable, valid, and sensitive tool for evaluating the health status of individuals with arthritis (1, 10–12).…”
Section: Introductionmentioning
confidence: 99%
“…13) AdoHcy potentiates tumor necrosis factor-induced cytotoxicity in human breast carcinoma cells, and is a competitive inhibitor of histone lysine methyltransferase in rat brain. 14,15) A recent report has suggested that histone H3 lysine 9 methylation is inhibited by increasing concentrations of AdoHcy. 16) Protein arginine methyltransferases such as PRMTs can be inhibited by another intermediate molecule in the methylation pathway, adenosine dialdehyde (AdOx).…”
mentioning
confidence: 99%